ADVANCE COMPUTER ARCHITECTURE - Jatiwal, Monika; Arora, Chetna; Arora, Charu (IJRDO -Journal of Computer Science Engineering, 2015)
This paper presents novel methods in teaching advanced computer architecturecourses. These methods include presenting fundamental computer architecture issuesemploying visual aids to teach fundamentals concepts like pipelining and processing.This paper studies about the history for Advance computer architecture. This paperexplains about the parallel processing, architecture of parallel processing, pipeliningand its role.